Planetary Period Oscillations of Saturn's Dayside Equatorial Ionospheric Electron Density Observed on Cassini's Proximal Passes. Issue 9 (8th September 2021) - Provan, G.; Cowley, S. W. H.; Bunce, E. J.; Milan, S. E.; Persoon, A. M.; Gurnett, D. A.
Abstract: We examine electron density data obtained in Saturn's dayside equatorial ionosphere during Cassini's proximal periapsis passes, specifically data derived from wave spectra, for evidence of modulation with the planetary period oscillations (PPOs) observed ubiquitously throughout Saturn's magnetosphere. Clear evidence is found on northern hemisphere inbound passes where northern system modulations occur in the ionospheric diffusive layer peaking at a factor of ∼7 at ∼3, 200 km altitude, extending at lesser factors to ∼7, 000 km altitude in the transport region. Simultaneous southern system modulations by factors ∼1.5–2.5 are also found above ∼3, 400 km. Factor of ∼4–10 northern system modulations are also detected in the diffusive layer and transport regions to ∼6, 000 km in the outbound pass data, though southern system modulations were not clearly discerned within the data scatter. Modulations were not detected in the photochemical equilibrium layer at altitudes ∼1, 600–2, 200 km. Where clear modulations were observed, their phases in the diffusive layer were close to those of the principal PPO meridians (determined previously from near‐apoapsis nightside magnetic data) for both systems, moving to somewhat earlier PPO phases by a few tens of degrees in the transport region. Comparison with magnetic oscillation phases determined directly from proximal pass data shows that electron density maxima occur ∼30°–50° earlier than azimuthal field maxima for both systems, ∼140°–160° earlier than colatitudinal field maxima for the northern system, nearer to antiphase than to leading quadrature, and ∼50°–70° later than colatitudinal field maxima for the southern system, somewhat less than lagging quadrature. Key Points: Saturn's equatorial ionospheric electron density data from Cassini's proximal orbits are examined for planetary period oscillations (PPOs) Northern and weaker southern PPO modulations occur in the diffusive layer and transport region (∼2, 500–10, 000 km) but not at lower altitudes Density maxima occur near the rotating principal meridians for both PPO systems, Ψ N, S ≈ 0°, with typical max/min ratios in the range ∼2–10